2014
DOI: 10.1111/1348-0421.12169
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole enhances immunity in ducklings vaccinated against Riemerella anatipestifer

Abstract: Oil-adjuvant-inactivated vaccine is one of the most cost-effective vaccines used to protect ducklings against RA infection; however, it does not provide complete protection in very young ducklings with immature immune systems. In the current study, LMS was used as an immunopotentiator to improve the immune system in ducklings. Serum immunoglobulin (Ig)G titers and the secretions of both Th1-type (IFN-g and IL-2) and Th2-type (IL-4 and IL-10) cytokines were higher in ducklings that had been vaccinated with LMS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consequently, chemotherapy is very important aspect in the treatment of ducks infected with R. anatipestifer [11]. A study conducted [12], showed levamisole to be a useful adjuvant in inactivated Riemerella vaccine and that it could enhance the immune response of ducklings and also alleviate local injection lesions by reducing the dose of the vaccine. A trivalent inactivated vaccine of R. anatipestifer, including serotype 1, 2, and 10 showed 100% protection in experimental animals from challenge with any of the three serotypes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, chemotherapy is very important aspect in the treatment of ducks infected with R. anatipestifer [11]. A study conducted [12], showed levamisole to be a useful adjuvant in inactivated Riemerella vaccine and that it could enhance the immune response of ducklings and also alleviate local injection lesions by reducing the dose of the vaccine. A trivalent inactivated vaccine of R. anatipestifer, including serotype 1, 2, and 10 showed 100% protection in experimental animals from challenge with any of the three serotypes [13].…”
Section: Discussionmentioning
confidence: 99%
“…RA infections cause major economic losses to the duck industry because of high mortality rates, low feed conversion and high treatment costs. In particular, the mortality rate has been reported to be as high as 70% in ducks with severe RA infections [1]. Currently, studies of RA have focused mainly on bacterial serotypes, virulence genes, detection methods and vaccine development [2e5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to that, the study conducted by Zhong et al, (2009) showed that the isolates were resistant to penicillin, ampicillin, tetracycline and sensitive to enrofl oxacin, chloramphenicol and neomycin. Gram's reaction -------Motility -------Growth microareobically -------Growth aerobically ----- Zhang et al (2014) stated the usefulness of levamizole as immunostimulant in the administration of adjuvanated vaccine. Zhong et al (2009) suggested that R. anatipestifer drug resistance profi les changed over time.…”
Section: Resultsmentioning
confidence: 99%